2010
DOI: 10.1016/s1130-1473(10)70059-2
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected angiographic and visual findings after clipping of a carotid-ophthalmic aneurysm

Abstract: SummaryA 56-year-old woman underwent surgery for a ruptured carotid-ophthalmic artery aneurysm. Intraoperative visual inspection confirmed that the ophthalmic artery was left intact. She had no light perception on the operated side right after surgery. Angiography one week after surgery confirmed exclusion of the aneurysm, no filling of the proximal portion of the ophthalmic artery, and a very faint filling of its distal orbital part. She gradually recovered from this deficit and 9 months after surgery she is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
1
0
0
Order By: Relevance
“…[27][28][29][30] In our cohort, 6 cases showed postoperative improvement of visual impairment and 1 case (2.63%) had new visual impairment, which is a lower incidence than previous estimations. Combined with previous surgical experience, we found that occlusion or vasospasm of the OphA during surgery, 31 ONrelated traction injury, and nourishing vessels of ON injury may cause visual field defects and decreased vision after surgery. 25 The process of abrasion of the ACP is important for avoiding visual complications because the drill may cause direct damage or thermal damage to the ON and vessels.…”
Section: Discussionsupporting
confidence: 67%
“…[27][28][29][30] In our cohort, 6 cases showed postoperative improvement of visual impairment and 1 case (2.63%) had new visual impairment, which is a lower incidence than previous estimations. Combined with previous surgical experience, we found that occlusion or vasospasm of the OphA during surgery, 31 ONrelated traction injury, and nourishing vessels of ON injury may cause visual field defects and decreased vision after surgery. 25 The process of abrasion of the ACP is important for avoiding visual complications because the drill may cause direct damage or thermal damage to the ON and vessels.…”
Section: Discussionsupporting
confidence: 67%